THE INFLUENCE OF USING SHOPEEPAY AND SHOPEE PAYLATER FEATURES ON SHOPEE USER PURCHASING DECISIONS DURING THE COVID- 19 - Sri Lestari; Naniek Utami Handayani; Manik Mahacandra (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
A process of buying and selling products, information and services that is carried out electronically by utilizing a computer network is often known as E-commerce and providing ease of payment, namely by using the ShopeePay and Shopee PayLater features. This study aims to find out which independent variables are variables that can influence purchasing decisions for Shopee users and find out which factors are more dominant in influencing purchasing decisions for Shopee users on the use of Shopeepay and Shopee PayLater features. Moreover, the trend of consumer behavior in the future also can be explored from the Zscore. The research method used is the method of Discriminant Analysis. The data collection technique was carried out by surveying 55 respondents through questionnaires. From the equation formed, consumers' tendency to buy or not to make purchases through Shopee E-Commerce is determined by the Customer Satisfaction variable in the transaction. Furthermore, from the Z value, the group that does not make purchases (0) has a Z value = 0.214, while the group that often makes purchases (1) has a Z = -0.207 value. From the equation formed, consumers' tendency to buy or not to make purchases through Shopee E-Commerce is determined by the Customer Satisfaction variable in the transaction. Moreover, from the Z value, the group that does not make purchases (0) has a Z value = 0.214, while the group that often makes purchases (1) has a Z = -0.207 value. From the equation formed, consumers' tendency to buy or not to make purchases through Shopee E-Commerce is determined by the Customer Satisfaction variable in the transaction. Furthermore, from the Z value, the group that does not make purchases (0) has a Z value = 0.214, while the group that often makes purchases (1) has a Z = -0.207 value.